1980
DOI: 10.1111/j.1348-0421.1980.tb02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Properties of Immune Interferon from Spleen Cell Cultures of Toxoplasma‐Infected Mice

Abstract: In response to antigenic stimulation, spleen cells from Toxoplasmainfected mice produce a factor showing inhibitory activity against vesicular stomatitis virus infection in L cell cultures. When BALB/C and ICR mice were inoculated intraperitoneally with the low-virulent S-273 strain of T. gondii, such activity was first detected in 4 and 7 days and reached maximum levels at 10 and 14 days respectively, and retained these levels for at least three weeks. However, BALB/C mice, which are considerably more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
(32 reference statements)
1
29
0
Order By: Relevance
“…One report described the inhibition of the growth of Toxoplasma and Besnoitia in hamster fibroblasts and kidney cells treated with supernatants derived from cultures of antigen-stimulated hamster lymphocytes (31). Inhibition of the growth of Toxoplasma in mouse L929 cells treated with supernatants obtained from cultures of antigen-stimulated mouse spleen cells has also been noted (32). The anti-Toxoplasma factor in this system had certain properties in common with interferon-y (32).…”
Section: Discussionmentioning
confidence: 86%
“…One report described the inhibition of the growth of Toxoplasma and Besnoitia in hamster fibroblasts and kidney cells treated with supernatants derived from cultures of antigen-stimulated hamster lymphocytes (31). Inhibition of the growth of Toxoplasma in mouse L929 cells treated with supernatants obtained from cultures of antigen-stimulated mouse spleen cells has also been noted (32). The anti-Toxoplasma factor in this system had certain properties in common with interferon-y (32).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, in a number of previous studies, various IFN preparations have also been reported to enhance the antimicrobial activity of different cell populations against other nonviral intracellular pathogens, including T. gondii (12)(13)(14)(15), Rickettsia akari (16), and Mycobacterium tuberculosis (17). In separate studies using the same monoclonal anti-IFN-y antibody and additional lymphokines and other IFN-y preparations (including pure, recombinant IFN-'y), we have also recently observed that the capacity of human monocyte-derived macrophages to respond to lymphokine with (a) enhanced oxidative burst activity and oxygen-dependent killing of T. gondii (18), and (b) oxygen-independent inhibition of in-tracellular Chlamydia psittaci and T. gondii replication (5,19) are both dependent upon and can be induced by IFN-y.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported that interferon blocked the growth of T. gondii in cultured fibroblast or epithelial cells (4)(5)(6). Shirahata and Shimizu (6) have presented evidence that IFN-y is the active substance in their studies of the inhibition of T. gondii. Experiments done in this laboratory showed that human recombinant IFN-a and IFN-,B had no effect on T. gondii.…”
mentioning
confidence: 99%